Cricket's Raining Champion: Two Decades of Duckworth–Lewis (and Stern). Issue 3 (29th May 2019) - Duckworth, Frank; Lewis, Tony; Stern, Steven
Abstract: When rain stops play in a cricket match, score targets are adjusted using the Duckworth-Lewis-Stern method. Twenty years after the original method was first approved for use in the Cricket World Cup, Frank Duckworth, Tony Lewis and Steven Stern recount the history and development of a game-changing idea